The effects of oleuropein on lung and heart injury in cecal ligation and puncture - induced sepsis - Hüseyin Serkan Erol; Tuba Aydın; Serkan Yıldırım; İsmail Can; Mesut Bünyami Halıcı (Eurasian Journal of Veterinary Sciences)
Aim: Sepsis is a fatal serious clinical disorder. The oxidative stress in sepsis plays an important role in the inflammation. Therefore, the effects of oleuropein (OLE) and ceftriaxone (CEFT) on sepsis were investigated in this study. Materials and Methods: Thirty male rats were divided into five equal groups: Sham, Sepsis, CEFT, OLE-150 and OLE-300, The 150 mg/kg of ceftriaxone (i.p.), and 150 and 300 mg/kg OLE (p.o.) were administered to the treatment groups fifteen minutes before the experiment. After 24 hours, blood samples, lungs and hearts tissues were taken. The creatine kinase (CK) and lactate dehydrogenase (LDH) activities in serum, lipid peroxidation (LPO), glutathione (GSH), superoxide dismutase (SOD) and catalase (CAT) levels were all determined. In addition, the expressions of the interleukin (IL)-8 in lung and tumor necrosis factor (TNF)-? in heart were pathologically and immunohistochemically were determined. Results: Sepsis caused significant increases in CK, LDH, LPO, GSH and heart CAT activity and caused inhibition of SOD and lung CAT activity (p<0.001). The OLE significantly decreased the LPO and GSH levels (p<0.001) and increased the SOD in activity of both tissues and CAT activity in lung tissue (p<0.001). Moreover, CEFT significantly decreased the LPO level (p<0.01) and increased tissue SOD and CAT activities in lung tissue (p<0.001). CK and LDH activities in serum showed marked decrease in OLE and CEFT groups (p<0.001). Conclusion: Antioxidant and a notable anti-inflammatory effect of OLE by reducing IL-8 and TNF-? levels have been stated. Thus, a strong antioxidant, such as OLE, would be beneficial for the treatment of sepsis.